Nutritional Status And Quality Of Life During Ramadan Among Higher Institute On Learning Centre Staffs With Different Body Weight Status - Mohd Adzim Khalili, Rohin; Intan Suhana Munira, Mat Azmi; Norhayati, Abd. Hadi (2014)
Ramadan fasting altersmeal time and frequency of food consumed. Meals are exclusively nocturnal and less frequent; consequently, this may affect energy and nutrient intake. It is proven that what we eat will affect our quality of life (QoL), which also influenced our selfidentification, social interactions, and psychological well-being.The aim of this study was to assess the total calorie and macronutrientsintake, as well as the quality of life (QoL), and also to investigate any correlationson quality of life (QoL) towards dietary intake before, during and after Ramadan among UniSZA staffs. This study was conducted in four phases; a week before Ramadan, first week of Ramadan, second week of Ramadan, and after Ramadan. The total of 55 UniSZA staffs was recruited.Qualitative analysis of food consumed showed that the percentage of energy as carbohydrates, protein, and fat remained unaffected by Ramadan fasting. Therewere significance difference (p< 0.05) in the mean score of physical functioning, role-physical, bodily pain, general health, and vitality. Results showed that there weresignificant correlations (p<0.05) between calorie and general health; carbohydrate and physical functioning; carbohydrate and vitality; protein and physical functioning; protein and general health; protein and vitality; as well as fat and vitality. In conclusion, this study has found no significant correlation between quality of life (QoL) and dietary intake during Ramadan among staffs in Institute of Higher Learning, UniSZA